2012
DOI: 10.1186/1471-2164-13-67
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum tolerance association mapping in triticale

Abstract: BackgroundCrop production practices and industrialization processes result in increasing acidification of arable soils. At lower pH levels (below 5.0), aluminum (Al) remains in a cationic form that is toxic to plants, reducing growth and yield. The effect of aluminum on agronomic performance is particularly important in cereals like wheat, which has promoted the development of programs directed towards selection of tolerant forms. Even in intermediately tolerant cereals (i.e., triticale), the decrease in yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 76 publications
(120 reference statements)
2
35
0
Order By: Relevance
“…Al tolerance in wheat was associated with 1 to 3 QTLs (Riede et al 1996;Ma et al 2006;Cai et al 2008;Navakode et al 2009). A study with triticale (Niedziela et al 2012) concluded that putative markers were associated with 3R, 4R, 6R and 7R chromosomes, which essentially confirm previous cytogenetic studies. Transporter genes are now widely recognized to regulate of malate and citrate excretion from root of wheat (and other plants), as the case is for the malate transporter ALMT1 gene (e.g.…”
Section: Mineral Toxicitysupporting
confidence: 82%
“…Al tolerance in wheat was associated with 1 to 3 QTLs (Riede et al 1996;Ma et al 2006;Cai et al 2008;Navakode et al 2009). A study with triticale (Niedziela et al 2012) concluded that putative markers were associated with 3R, 4R, 6R and 7R chromosomes, which essentially confirm previous cytogenetic studies. Transporter genes are now widely recognized to regulate of malate and citrate excretion from root of wheat (and other plants), as the case is for the malate transporter ALMT1 gene (e.g.…”
Section: Mineral Toxicitysupporting
confidence: 82%
“…Currently, association mapping methods has been used in diverse plant species such as bread wheat (Yu et al, 2012;Phumichai et al, 2012), barley (Cockram et al, 2008), triticale (Niedziela et al, 2012) and bean (Shi et al, 2011). For molecular studies, there should be a reasonable degree of variability present among the organism of interest; only then the molecular approaches can identify the genetic case underlying this variability.…”
Section: Discussionmentioning
confidence: 99%
“…It is a powerful technique used to identify genomic regions linked to specific variants of a phenotypic trait (Saeed et al, 2014). Genome-wide association in plants has wide range of use and there are many reports of association studies on many crops such as barley (Gutiérrez et al, 2011;Cockram et al, 2010), rice (Shao et al, 2011), bread wheat (Yu et al, 2012), maize (Poland et al, 2011), triticale (Niedziela et al, 2012), bean (Shi et al, 2011), sugar beet (Würschum et al, 2011), cotton fiber quality traits (Abdurakhmonov et al, 2009) and cotton salinity stress tolerance (Saeed et al, 2014). Cotton Gossypium spp.…”
Section: Introductionmentioning
confidence: 99%
“…Genotypes of triticale have demonstrated different reaction in the presence of Al 3+ toxicity in trials using nutrient solution (Camargo et al, 2006;Niedziela et al, 2012). This technique has been used in winter cereal breeding programs due to the difficulty presented to evaluate the tolerance to Al 3+ toxicity in field, demonstrating great representativeness when associated to the field condition (Portaluppi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%